A difusão de representações sociais dos direitos humanos pelo jornal nacional - Santos, Anderson Mathias Dias (2014)
Several researches have shown the role of the press, especially television, to form and diffuse social representations and the importance of TV news as a source of information about human rights. In the present study, we analyzed the social representations of human rights diffused by the TV news program with the largest audience in Brazil Jornal Nacional. We aimed to verify: what human rights were diffused by the Jornal Nacional; how the rights were clustered; the differences in Jornal Nacional s coverage according to the class of human rights and; if there was variability on defense of the human rights according the kind of right. The sample consisted of 277 news and reports from 54 consecutive editions of Jornal Nacional between 04/16/2012 and 06/16/2012. A total of 1022 news and reports, were selected from the Jornal Nacional s website, containing contents of Human Rights, with the exception of international, sports and politics reports. After preparing the corpus, this was examined by Alceste software. Among the results we observed clustering of the sample into four classes: Crimes against Individual Rights, corresponding to 31% of UCEs selected and included the right to life, against the violation of the body and safety. This class mainly emphasized the violation of individual rights. It was characteristic of the coverage of these events using short and decontextualized news; Economic Aspects of Rights which corresponded to 33 % of the UCEs selected and included the rights to the environment, labor and consumer. Were characteristics of this class using the economic argument as a form of awareness and using the statistics. The main approach in this class was use short news followed by an explicative report; Rights relating to Transit with 24% of the UCEs selected and included the rights of traffic safety, public transportation and strikes. The covers of this class are characterized mainly by the criticism of rights violations in the case of the right of traffic safety. The right to public transportation, the criticism was about disorders caused by strikes by employees of public transport companies in several cities in Brazil and disorders; Rights of Protection against Disasters, which amounts to 12 % of the UCEs selected, includes news and reports about tragedies, notably, drought in the northeast of Brazil and floods in Amazon. In both tragedies, the focus was on the suffering of residents of such tragedies. The type of coverage in this class ranged between detailed reports and news followed by reports. Through the literature on the theory of social representations, human rights and media, we discussed the differences presented by television news coverage according to the classes of rights, promotion of consensual rights and avoidance of the controversial, the use of experts on topics related to the economy and the appeal to the suffering of disaster victims.